Development of Off-Grid Solar Power Plant Model and Monitoring System for Renewable Energy Education - Eliza; Marwan Rosyadi (P3KM Politeknik Pertanian Negeri Samarinda, 2025)
The increasing demand for energy has accelerated the need for sustainable and eco-friendly alternatives, including the adoption of off-grid Solar Power Systems (PLTS). This study aims to evaluate the performance of a 1.2 kWp off-grid photovoltaic solar power system and to develop an Internet of Things (IoT)–based monitoring system as an educational tool for renewable energy learning at SMKN 1 Majalaya. The system is constructed using six 200 Wp solar modules, a 12 V 100 Ah VRLA battery, a 1000 W inverter, and two types of solar charge controllers, namely PWM and MPPT. For monitoring purposes, an ESP32 microcontroller integrated with a PZEM-004T sensor is employed to measure voltage, current, power, and energy in real time through a web-based dashboard. The testing results indicate that daily energy production ranges from 4.84 to 5.08 kWh, with an overall system efficiency of approximately 84.5%. The IoT-based monitoring system demonstrates stable and accurate data acquisition, consistent with manual measurements and simulation results using Helioscope and GSA. The off-grid PLTS system effectively supplies power for light to medium electrical loads, making it suitable for practical applications in educational environments. Furthermore, the integration of IoT technology enhances students’ understanding of renewable energy systems, performance analysis, and digital monitoring techniques. Overall, this system not only serves as a functional alternative energy source but also provides a valuable and innovative learning resource for developing students’ competencies in future energy technologies.